Perancangan Aplikasi Mobile Android Dalam Program Mitigasi Bencana (Studi Kasus Disaster Management Center Dompet Dhuafa) - Aulia Agustina Anjani; Meivi Kartikasari; Chaulina Alfianti Oktavia (Prosiding SISFOTEK, 2023)
Disasters are a series of events caused by natural and non-natural factors that result in environmental damage, loss of property, and psychological impacts. Natural disasters include earthquakes, tsunamis, volcanic eruptions, floods, droughts, and landslides, necessitating disaster mitigation efforts to minimize their effects. One such effort is the Disaster Management Center at Dompet Dhuafa, serving as the frontline in disaster response. During disaster management, Dompet Dhuafa's Disaster Management Center faces challenges such as a lack of public awareness about disaster-prone areas, a shortage of volunteer resources for disaster response, and reliance on manual reporting systems. The goal of this research is to develop an application that streamlines the reporting process for the Disaster Management Center at Dompet Dhuafa. Problem analysis in this study utilizes a fishbone diagram to identify issues, and system design employs UML diagrams, including use cases, activity diagrams, and sequence diagrams. The outcome of this research is an application that facilitates public access to information about disaster-prone areas and disaster reporting. Additionally, the application aids volunteers in reporting their activities while in the field. Black box testing is used to evaluate the application.